Mediation Analysis Using the Hierarchical Multiple Regression Technique: A Study of the Mediating Roles of World-Class Performance in Operations - Ciptono, Wakhid S.; Ibrahim, Abdul Razak; Sulaiman, Ainin (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
The changing environment in an organization is forcing the organization to find a plan of integrated management framework and adequate performance measurement. Failure to plan basically means planning failure for the business. Finding the critical factors of quality management practices (QMP), themediating roles of the contextual factors of world-class performance in operations (i.e., world-class company practices or WCC, operational excellence practices or OE, company nonfinancial performance or CNFP), and the company financial performance would enable the company to facilitate the sustainability of TQM implementation model.This empirical study aims to assess how TQMâa holistic management philosophy initially developed by W. Edward Deming, which integrates improvement strategy, management practices, and organizational performanceâis specifically implemented in the oil and gas companies operating in Indonesia. Relevant literature on the TQM, the world-class performance in operations (world-class company and operational performance), the company performance (financial and non-financial performances), and the amendments of the Law of the Republic of Indonesia concerning the oil and gas industry, and related research on how the oil and gas industry in Indonesia develops sustainable competitive advantage and sustainable development programs are reviewed in details in our study. The findings from data analysis provide evidence that there is a strong positive relationship between the critical factors of quality management practices and the company financial performance mediated by the three mediating variables, i.e., world-class company practices, operational excellence practices, and company non-financial performance.